STOCK INVESTMENT DECISION ANALYSIS ON INVESTORS IN SURABAYA - Sihotang, Albertus Evanelian; Pertiwi, Tri Kartika (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
This study aims to empirically prove the impact of overconfidence, risk perception, loss aversion, and herding behavior on stock investment decisions in the city of Surabaya. The population in this research were stock investors in the city of Surabaya who found 87,702 people, with a sample of 135 people obtained through purposive sampling technique. The analysis method of this research uses Partial Least Square. According to the results of research that has already done, overconfidence has a significant positive effect on investment decisions, risk perception has a significant positive effect on investment decisions, loss aversion has no significant positive effect on investment decisions, herding behavior has a positive effect on investment decisions.